1
$\begingroup$

... For example, if we write $\dfrac{\operatorname dy}{\operatorname dx} = \dfrac{-x}{y}$ in polar coordinates, we obtain the equation $\dfrac{\operatorname dr}{\operatorname d\theta} = 0$ whose solution is $r = C$.

Seems like a straightforward statement, but I don't seem to get there. I guess i'm doing something wrong... Could someone help?

If $x = r\cos \theta$, $y=r \sin \theta$ with the inverse transformation $r = \sqrt{x^2+y^2}$, $\theta = \arctan \dfrac{y}{x}$.

Then $\dfrac{-x}{y} = \dfrac{-\cos \theta}{\sin \theta}$

Next:

$$\dfrac{\operatorname dy}{\operatorname dx} \stackrel{\color{red}{(1)}}{=} \dfrac{\operatorname dy}{\operatorname dr}\cdot \dfrac{\operatorname dr}{\operatorname d\theta}\cdot \dfrac{\operatorname d\theta}{\operatorname dx} = \sin \theta \cdot \dfrac{\operatorname dr}{\operatorname d\theta}\cdot \dfrac{-r\sin \theta}{r^2}$$

This results in:

$$\sin \theta \cdot \dfrac{\operatorname dr}{\operatorname d\theta}\cdot \dfrac{-r\sin \theta}{r^2} = \dfrac{-\cos\theta}{\sin \theta}$$

or

$$\dfrac{\operatorname dr}{\operatorname d\theta}= \dfrac{r \cos\theta}{\sin^3 \theta}$$

Fault?

I suspect $\color{red}{(1)}$ is not right. Since $\dfrac{\operatorname dy}{\operatorname d r}$ doesn't make any sense. I should be using something like $\partial$, but how exactly?

$\endgroup$
2
  • $\begingroup$ I remember having similar problem,a quick revision of chain rule should make it clear. Please see this question math.stackexchange.com/questions/84736/… $\endgroup$
    – SomeOne
    Apr 29, 2015 at 21:16
  • $\begingroup$ Indeed, $(1)$ does not make sense because $r$ and $\theta$ are independent variables. $\endgroup$
    – Alex M.
    Apr 29, 2015 at 21:40

3 Answers 3

2
$\begingroup$

The fault is in: $\frac{dy}{dx}=\frac{dy}{d\theta}\frac{d\theta}{dx} + \frac{dy}{dr}\frac{dr}{dx} $

$\endgroup$
1
$\begingroup$

$$\frac{dy}{dx}=\frac{dy}{d\theta}\times\frac{d\theta}{dx}=\frac{\frac{dy}{d\theta}}{\frac{dx}{d\theta}}\tag{1}$$$$x=r\cos(\theta)$$$$\therefore\frac{dx}{d\theta}=\cos(\theta)\frac{dr}{d\theta}-r\sin(\theta)\tag{2}$$$$y=r\sin(\theta)$$$$\therefore\frac{dy}{d\theta}=\sin(\theta)\frac{dr}{d\theta}+r\cos(\theta)\tag{3}$$Substituting (2) and (3) into (1) then gives:$$\frac{dy}{dx}=\frac{\sin(\theta)\frac{dr}{d\theta}+r\cos(\theta)}{\cos(\theta)\frac{dr}{d\theta}-r\sin(\theta)}$$Hopefully you can proceed from here...


The mistakes you made were in the calculations of $\frac{dy}{dr}$ and $\frac{dx}{d\theta}$:$$\frac{dy}{dr}=\sin(\theta)+r\cos(\theta)\frac{d\theta}{dr}$$$$\frac{dx}{d\theta}=-r\sin(\theta)+\cos(\theta)\frac{dr}{d\theta}$$Using these in your approach would have led to the same result as I got above, i.e.:$$\frac{dy}{dx}=\frac{dy}{dr}\cdot\frac{dr}{d\theta}\cdot\frac{d\theta}{dx}$$$$=\left(\sin(\theta)+r\cos(\theta)\frac{d\theta}{dr}\right)\cdot\frac{dr}{d\theta}\cdot\left(\frac{1}{-r\sin(\theta)+\cos(\theta)\frac{dr}{d\theta}}\right)$$$$=\frac{\sin(\theta)\frac{dr}{d\theta}+r\cos(\theta)}{\cos(\theta)\frac{dr}{d\theta}-r\sin(\theta)}$$

$\endgroup$
0
$\begingroup$

You could also view your problem as an equality of differential forms: $x\mathbb{d}x + y\mathbb{d}y =0$. Since $\mathbb{d}x=\mathbb{d}(r\cos \theta)=\cos \theta \mathbb{d}r-r \sin \theta \mathbb{d}\theta$ and $\mathbb{d}y= \sin \theta \mathbb{d}r+ r \cos \theta \mathbb{d} \theta$, a simple substitution makes this is equivalent to $0= r \cos^2 \theta \mathbb{d} r - r^2 \sin \theta \cos \theta \mathbb{d}\theta + r \sin^2 \theta \mathbb{d}r + r^2 \sin \theta \cos \theta \mathbb{d}\theta = r \mathbb{d}r$, which means $\mathbb{d}r=0$ which gives $r=constant$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.